The impact of collateral therapeutics on stroke hemodynamics in normotensive and hypertensive rats: a step toward translation - Cipolla, Marilyn J.; Hunt, Ryan D.; Liebeskind, David S.; Tremble, Sarah M. (Frontiers in Neurology, 2024)
Stroke interventions that increase collateral flow have the potential to salvage penumbral tissue and increase the number of patients eligible for reperfusion therapy. We compared the efficacy of two different collateral therapeutics during transient middle cerebral artery occlusion (tMCAO) in normotensive and hypertensive rats. The change in collateral and core perfusion was measured using dual laser Doppler in response to either a pressor agent (phenylephrine, 10 mg/kg iv or vehicle) or a collateral vasodilator (TM5441, 5 mg/kg iv or vehicle) given 30 minutes into tMCAO in male Wistar and Spontaneously Hypertensive Rats (SHR). Pressor therapy increased collateral flow in Wistar but was ineffective in SHR.The increase in collateral flow in Wistar rats was associated with impaired cerebral blood flow autoregulation (CBFAR) that was intact in SHR. TM5441 caused a decrease in collateral perfusion in Wistar rats and a modest increase in SHR. Pressor therapy reduced early infarction in both groups but increased edema in SHR whereas TM5441 did not have any beneficial effects in either group. Thus, pressor therapy was superior to a collateral vasodilator in increasing collateral flow and improving outcome in Wistar rats likely due to pial collaterals that were pressure passive; the lack of CBF response in SHR to pressor therapy was likely due to intact CBFAR that limited perfusion. While TM5441 modestly increased CBF in SHR, but not Wistar, it did not have a beneficial effect on stroke outcome.These results suggest that collateral therapies may need to be selected for certain comorbidities.